Children, teens and the new technologies: ICT’ access and use in Peruvian schools (Revista Peruana de Investigación Educativa, 2014)
The intense distribution of educational technologies in Peruvian schools in the last decade along with a greater availability of ICT in the market (thanks to its affordability and greater presence) seems to be changing the technological landscape in Peruvian schools. This paper deals with the question of how this massive presence of ICT is appropriated in the school scenario and what are the students’ perspectives on this. It departs form a recent study in three Peruvian regions, in six different communities, both rural and urban, and carried out in primary and secondary schools. It explores mainly students’ access to ICT and how they use ICT inside and outside schools. Other actors’ (such as teachers and principals) perspectives are also considered to understand and place into context the students’ experiences. The study reveals the precariousness in students’ access to educational technologies, despite their very presence in schools. It also shows the limited use of ICT in students’ learning processes inside and outside schools.
Keywords: children; teens; Information and Comunication Technologies (ICT); educational technologies; Peru